2020
DOI: 10.1016/j.redox.2020.101633
|View full text |Cite
|
Sign up to set email alerts
|

Low-protein/high-carbohydrate diet induces AMPK-dependent canonical and non-canonical thermogenesis in subcutaneous adipose tissue

Abstract: Low-protein/high-carbohydrate (LPHC) diet has been suggested to promote metabolic health and longevity in adult humans and animal models. However, the complex molecular underpinnings of how LPHC diet leads to metabolic benefits remain elusive. Through a multi-layered approach, here we observed that LPHC diet promotes an energy-dissipating response consisting in the parallel recruitment of canonical and non-canonical (muscular) thermogenic systems in subcutaneous white adipose tissue (sWAT). In particular, we m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…The pathway of the AMPK-PGC1α axis is believed to function as a metabolic sensor involved in the regulation of brown or beige adipogenesis . AMPK, as the “fuel switch” and “energy receptor”, is the protein kinase most sensitive to energy metabolism . Herein, our results showed that the expressions of AMPK and PGC1α proteins of iBAT in HFD-fed mice were significantly elevated after the treatment with 800 mg/kg TB ( p < 0.05), where the AMPK-PGC1α signaling pathway was also activated by TB in the iWAT of the tested mice, consistent with the results of iBAT.…”
Section: Discussionmentioning
confidence: 59%
“…The pathway of the AMPK-PGC1α axis is believed to function as a metabolic sensor involved in the regulation of brown or beige adipogenesis . AMPK, as the “fuel switch” and “energy receptor”, is the protein kinase most sensitive to energy metabolism . Herein, our results showed that the expressions of AMPK and PGC1α proteins of iBAT in HFD-fed mice were significantly elevated after the treatment with 800 mg/kg TB ( p < 0.05), where the AMPK-PGC1α signaling pathway was also activated by TB in the iWAT of the tested mice, consistent with the results of iBAT.…”
Section: Discussionmentioning
confidence: 59%
“…Estrogen can also modulate BAT development and thermogenesis via the hypothalamic adenosine monophosphate-activated protein kinase (AMPK) signaling pathway 49 . AMPK activation can stimulate Ca 2+ cycling thermogenesis 50 . We observed significantly increased lactotransferrin (TRFL), which decreases the activity of the AMPK complex 51 .…”
Section: Discussionmentioning
confidence: 99%
“…AMPK α is well known as an energy sensor in eucaryotic cells and plays critical roles in controlling systemic metabolic homeostasis [ 52 , 53 ]. However, emerging studies have revealed that AMPK α is also implicated in regulating oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%